ملامح التجربة الصوفية في رواية " الأطلسي التائه" لمصطفى لغتيري - العابد، صباح, قدوري، فاطمة (جامعة الوادي Universty of Eloued, 2019)
تندرج هذه الدراسة في سياق محاولة البحث عن ملامح التجربة الصوفية في رواية " الأطلسي التائه " لمصطفى لغتيري، إذ تحاول هذه الدراسة الوقوف على مفهوم التصوف حيث أنه عالم روحي يدعو إلى تزكيّة النّفس والانعتاق من أسوار المادة والاهتمام بالجوهر، الذي يعتبر سبيلاً لكشف الوجود، وهذا لا يكون إلاّ بالممارسة الفعلية والاجتهاد في التربية الروحية والسّلوك، ومنه الوقوف على تعريف التجربة الصوفية فهي تجربة تنطلق من الداخل من عمق الذات الانسانية لا من خارجها وهي مشروع تحرر الانسان من القيود وذلك من أجل معرفة الذات والوجود معرفة حقيقية. فرواية الاطلسي التائه وظفت التراث الصوفي، وفيها تداخل السرد مع التصوف، وذلك باستحضار الروائي لشخصية أبو يعزى الهسكوري ملامح التجربة الصوفية من خلال اسماء الشخصيات في الرواية، بالإضافة إلى المكان والزمان والتاريخ. اعتمدنا في هذه الدراسة على المنهج التأويلي التاريخي. This study deals with the concept of Sufism as it is a spiritual world that calls for self-affirmation and freedom from the walls of matter and attention to the essence, which is a way to reveal existence, and this It is only an attempt to practice the spirit of spiritual education and behavior, and from it to stand on the definition of the Sufi experience is an experience that begins from the inside of the depth of the human self, not from outside it, the project of freeing the human from the restrictions in order to know the self and existence of real knowledge. The story of the lost Atlantic and the Soviet heritage, and the overlap of narration with Sufism, by recalling the novelist of the character of Abu Hesba Haskouri features of the Sufi experience through the names of characters in the novel, in addition to place, time and history. In this study, we adopted the historical method of interpretation
Keywords: التصوف – ملامح التجربة الصوفية – الأحوال والمقامات.; Sufism - Characteristics of Sufi Experience - Conditions and positions